Full-Length Infectious Clones of Two New Isolates of Tomato Mosaic Virus Induce Distinct Symptoms Associated with Two Differential Amino Acid Residues in 128-kDa Protein - Choi, Go-Woon; Oh, June-Pyo; Cho, In-Sook; Ju, Hye-Kyoung; Hu, Wen-Xing; Kim, Boram; Seo, Eun-Young; Park, Jong-Seok; Domier, Leslie L; Hammond, John; Song, Kihak; Lim, Hyoun-Sub (The plant pathology journal, 2019)
In 2017, two new tomato mosaic virus (ToMV) isolates were collected from greenhouses in Buyeo, Chungcheongnam-do, South Korea. Full-length cDNAs of the new ToMV isolates were cloned into dual cauliflower mosaic virus 35S and T7 promoter-driven vectors, sequenced and their pathogenicities investigated. The nucleotide sequences of isolates GW1 (MH507165) and GW2 (MH507166) were 99% identical, resulting in only two amino acid differences in nonconserved region II and the helicase domain, Ile668Thr and Val834Ile. The two isolates were most closely related to a ToMV isolate from Taiwan (KJ207374). Isolate GW1 (Ile668, Val834) induced a systemic hypersensitive response in Nicotiana benthamiana compared with the isolate GW2, which a single residue substitution showed was due to Val834.In 2017, two new tomato mosaic virus (ToMV) isolates were collected from greenhouses in Buyeo, Chungcheongnam-do, South Korea. Full-length cDNAs of the new ToMV isolates were cloned into dual cauliflower mosaic virus 35S and T7 promoter-driven vectors, sequenced and their pathogenicities investigated. The nucleotide sequences of isolates GW1 (MH507165) and GW2 (MH507166) were 99% identical, resulting in only two amino acid differences in nonconserved region II and the helicase domain, Ile668Thr and Val834Ile. The two isolates were most closely related to a ToMV isolate from Taiwan (KJ207374). Isolate GW1 (Ile668, Val834) induced a systemic hypersensitive response in Nicotiana benthamiana compared with the isolate GW2, which a single residue substitution showed was due to Val834.